Association of asparagine in saliva with a lower risk of early childhood caries in undernourished children: a cross-sectional study - Lima, P. H.M.; Mota, A. C.M.; Lima, V.; Cidrao, G. P.; Toyama, D. O. [UNESP]; Toyama, M. H. [UNESP]; Fonteles, C. S. (Springer Nature, 2025)
Aim: The aim was to investigate the salivary amino acid profile in children with protein-energy undernutrition (PEU) and its association with caries experience in the presence of other risk factors. Methods: The study had a cross-sectional design and was carried out with 122 children (12–71 months old), classified according to their level of undernutrition (mild—GI, n = 22; moderate—GII, n = 53) or healthy controls (GC, n = 47). The children were categorized based on the presence of caries into caries-experienced groups (ceos > 0, 22 CG, 12 GI and 18 GII) and caries-free groups (ceos = 0, 25 CG, 10 GI and 36 GII). Total unstimulated and stimulated saliva were collected to determine amino acids and Streptococcus mutans, respectively. Results: Eighteen amino acids were associated with PEU. Undernutrition and caries experience influenced the presence of the following amino acids: L-anserine, asparagine, ethanolamine, gamma-aminobutyric acid, and norleucine. Asparagine was a significant predictor of a lower probability of caries experience in a logistic regression model. Conclusions: Salivary amino acids are associated with undernutrition in children, and the presence of asparagine in saliva relates to a lower caries risk.
Keywords: Amino Acids; Caries; Child Nutrition Disorders; Protein Energy Malnutrition; Saliva